Water Contaminated Fresh Tephra as a Natural Hazard Factor: the 2008-2009 Eruption of Koryakskii Volcano, Kamchatka - Melekestsev I.V.; Kartasheva E.V.; Kirsanova T.P.; Kuzmina A.A. (My University, 2011)
Abstract-This study is the first to show, using data from the eruption of Koryakskii Volcano, Kamchatka that began in December 2008 and continued through 2009 that the water in permanent and temporary streams that start on the slopes of the volcanic cone and in temporary lakes when contaminated with fresh tephra is a specific hazard factor related to long-continued hydrothemial-phreatic eruptions on that volcano. This water is characterized by increased acidity (pH 4.1-4.35) and large amounts (up to 50-100 cm /liter) of solid suspension and is unfit for drinking and irrigation. When combined with tephra, it probably produced mass destruction of a number of animals who lived on the slopes and at the base of the volcano. The water contaminated with tephra is an important component of the atmospheric mud tlows occurring on Koryakskii Volcano; for several future years it will be a potential source for enhancing the acidity of ground water in the volcanic edifice.
Keywords: 38.37.25 Вулканология; Корякский; Kamchatka